Association between sleep quality and weight gain in pregnancy: a cross-sectional study - Roberto, Ana Paula Santos Costa [UNESP]; Parenti, Ana Beatriz Henrique [UNESP]; de Barros Gomes, Caroline [UNESP]; Carvalhaes, Maria Antonieta de Barros Leite [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP] (Springer Nature, 2024)
Introduction: There are grounds for the hypothesis that poor sleep quality, regardless of the pre-gestational nutritional status, is a risk factor for inadequate gestational weight gain. Objective: To investigate the association between sleep quality and insufficient or excessive gestational weight gain in Brazilian pregnant women without gestational complications and monitored in public prenatal care units. Methods: This is a cross-sectional study nested within a cohort study that reviewed pregnant women’s mental health, sleep, and nutritional outcome. Data collection was carried out from May 2018 to June 2019 through face-to-face and telephone interviews and consultation of pregnant women’s medical records. Sleep quality was assessed using the Mini-sleep Questionnaire. The pregnancy weight gain was measured based on the Institute of Medicine’s recommendations. Univariate and multivariate Poisson regression analysis was used for the two outcomes: insufficient or excessive weight gain, using pregnant women with adequate weight gain as the reference category. Associations were considered significant when p < 0.05. Results: The prevalence of severe sleep disorders was high: 63.4% of pregnant women experienced this condition. Severe sleep disorders enhanced independently the risk of insufficient gestational weight gain (PR = 2.40; 95% CI = 1.06–5.42, p = 0.035). There was no association between sleep disorders and excessive gestational weight gain. Conclusion: The hypothesis that poor sleep quality influences gestational weight gain was confirmed. Severe sleep disorders, a highly prevalent condition, significantly increased the prevalence of insufficient gestational weight gain, yet it was not associated with excessive weight gain. Thus, educational actions should be included in the preconception and prenatal periods, in order to encourage the adoption of habits that favor sleep quality, an intervention that may have positive effects in reducing insufficient gestational weight gain.
Keywords: Gestacional weight gain; Pregnancy; Prenatal care; Sleep quality